Investigation of Passive Filter Performance on Three Phase DC to AC Converter - S.Z. Mohammad Noor; N. Rosmizi; N. Aminudin; Faranadia A.H (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This work presents investigation of passive filter performance on three-phase inverter with 180° conduction mode. The simulation model of the inverter is developed by using MATLAB/Simulink. The power circuit used Insulated Gate Bipolar Transistor (IGBT) as switching device. The inverter is controlled by using bipolar Sinusoidal Pulse Width Modulation (SPWM) technique. The IGBT was set to 25 kHz for switching frequency (fs). Three types of passive filters which are LC, RC and PI filters are used to investigate the ability to remove the unwanted signal that occurred on the inverter. The result is analyzed based on the performances of output filter in term of Total Harmonic Distortion in voltage (THDv), current (THDi), shape of output voltage and current. The THD must be less than 5% at rated inverter output voltage or current by referring to IEC 61727 Standard. The passive filter is modeled in MATLAB/Simulink environment to study the characteristics and performance of the filters.